A molecular dynamic study of change in thermodynamic functions of silicon FCC cell with the change in temperature (Journal of Naval Architecture and Marine Engineering, 2017)
In modern days silicon is being extensively used in making electronic semiconductor-based chips and ICs. In this research, the change in different thermodynamic properties of silicon like lattice heat capacity, molar enthalpy and Debye temperature at constant pressure, with the change in temperature, has been investigated by using molecular dynamics (MD) simulation method. Knowing silicon thermodynamic functions are quite important, because many electronic companies are nowadays trying a lot to reduce the heat generated by their semiconductor chips as excessive heating of the chip not only warms up the device quickly but also reduces the chip life. The results obtained from this simulation help engineers to design electronic chips more efficiently. For simulation Accelrys Materials Studio (Version 5.0) software has been used. The simulation was run for silicon FCC diamond structured cell. The analysis tool used in the simulation is known as CASTEP (Cambridge Sequential Total Energy Package). This tool is specialized for performing molecular level thermodynamic analysis to generate data and graphs for the change in different temperature dependent properties of the molecular system. The interaction between silicon atoms was expressed by the Kohn-Sham potential and MD calculation was conducted on crystalline state of silicon at temperatures between 0 and 1000 K. Here, density function theory (DFT) based tool has been used to derive density of state relations. Results obtained by the simulation were compared with published experimental values and it was found that the simulation results were close to the experimental values.